UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN MELALUI BIMBINGAN BERKELANJUTAN DI SDN 15 SUNGAI NYALO - Nasrijon Nasrijon (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACTThis research starts from learning planning is a very important step before the implementation of learning. Careful planning is needed so that the implementation of learning runs effectively. Learning planning is outlined in the Learning Implementation Plan (RPP). For this reason, it is necessary to increase the competence of teachers in preparing the RPP. The researcher tries to use continuous learning to improve the competence of teachers in preparing RPP. Based on the results of ongoing guidance research can improve the competence of teachers in preparing RPP. This can be evidenced from the results of observations / observations which show that there is an increase in teacher competence in preparing RPP from cycle to cycle. In the first cycle the average value of RPP components was 69% and 83% in the second cycle. So, there was an increase of 14% from cycle IKeywords: Teacher Competence, RPP, Continuing Guidance